Mapping of surface radiogenic heat production from in situ gamma spectrometry and chemical data of exhumed mantle peridotites at the St. Peter and St. Paul archipelago (equatorial Atlantic). (February 2023) - Ferreira da Costa Campos, Thomas; Araujo, José Humberto; Sichel, Susanna Eleonora; Pastura, Valéria Fonseca da Silva; Motoki, Kenji Freire; Mairink Barão, Leonardo; Maia, Marcia; Monteiro da Fonseca, Estefan; Navoni, Julio; Vargas, Thais; Szatmari, Peter; Brunelli, Daniele
Abstract: This work presents the first mapping of the radiogenic heat production (RHP) and the respective radiogenic heat flow (RHF) of the Saint Peter and Saint Paul Archipelago (SPSPA) located at 1°N in the Equatorial Atlantic Ocean. Using radiogenic heat producing elements (RPE) we inferred a radiogenic heat production ranging 0.08–0.68 μW/m 3 (Median: 0.21 μW/m 3 and Geometric mean: 0.25 μW/m 3 ) by whole-rock chemical analysis and between 0.08 and 0.48 μW/m 3 (Median: 0.19 μW/m 3 ; Geometric mean: 0.19 μW/m 3 ) by in situ Gamma radiation spectrometry. The mean of radiogenic heat production of mylonite rocks from SPSPA (0.22 μW/m 3 ) is significantly higher than predicted values for ultramafic rocks as those largely outcropping in the SPSPA. This is probably due to the pervasive alteration of these rocks and the incorporation of little magma fractions during mylonitization. By converse, the average surface radiogenic heat flow (49.7 μW/m 2 ) is lower than that predicted for the oceanic lithosphere, suggesting that the upper mantle contribution to the heat flow is also low in the SPSPA region. Based on the acquired data and the peculiar tectonics of the SPSPA we propose that the lithospheric mantle around the SPSPA area is colder than that surrounding the Equatorial Atlantic region. Highlights: Surface Radioactive Heat Production and Heat Flow in abyssal mantle rock. Serpentinization, carbonatation process and the hydration of mantle wedge. Serpentinized mantle rock enriched in some incompatible and fluid-mobile elements. Fluid-mobile elements transferred to the mantle wedge by hydrothermal fluids deriving from seawater and oceanic crust.